2022
DOI: 10.1101/2022.03.04.482364
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Feeding desensitizes A1 adenosine receptors in adipose through FOXO1-mediated transcriptional regulation

Abstract: Adipose tissue is a critical regulator of energy balance that must rapidly shift its metabolism between fasting and feeding to maintain homeostasis. Adenosine has been characterized as an important regulator of adipocyte metabolism primarily through its actions on A1 adenosine receptors (A1R). We sought to understand the role A1R plays in adipocytes during fasting and feeding to regulate glucose and lipid metabolism by using an inducible, adiponectin-Cre with Adora1 floxed mice (FAdora1−/−), where F designates… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…Then, the activated immune system further generates reactive oxygen species (ROS) and cytokines which can further give rise to worsening lung injury [12]. AKT/Foxo1 signaling pathway possesses multiple regulators as well as effectors including glucose, insulin, cytokines, and growth factors, displaying significant functions in cell survival, metabolism, inflammation, and oxidative stress [13][14][15][16]. Previous studies have demonstrated that changes in AKT activity levels in macrophages show significant impacts on polarization and activation of macrophages via regulating Foxo1 activity during ARDS [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the activated immune system further generates reactive oxygen species (ROS) and cytokines which can further give rise to worsening lung injury [12]. AKT/Foxo1 signaling pathway possesses multiple regulators as well as effectors including glucose, insulin, cytokines, and growth factors, displaying significant functions in cell survival, metabolism, inflammation, and oxidative stress [13][14][15][16]. Previous studies have demonstrated that changes in AKT activity levels in macrophages show significant impacts on polarization and activation of macrophages via regulating Foxo1 activity during ARDS [17,18].…”
Section: Introductionmentioning
confidence: 99%